Pengelolaan Tenaga Kerja Difabel untuk Mewujudkan Workplace Inclusion - Poerwanti, Sari Dewi (INKLUSI, 2017)
The focus of this study is the management of workers with disabilities as efforts to achieve an inclusive workplace in PT. Trans Retail Indonesia. The study also elaborates supporting and inhibiting factors in the implementation of labor management. This is a qualitative research that collects the data using literary studies, observation and in-depth interview. The result shows that the management is started from knowledge level of the company about workers with disabilities, selection process, development, compensation and maintaining the employs. In addition, they identify key factors of managing different ability such as stakesholders, associate support, mentoring and counseling for workers with disabilities. The obstacles of managing workers with disabilities include professionalism, communication, and productivity that lead to an attempt of firing. Overall, PT. Trans Retail Indonesia can be classified as one with ability to develop diversity management in order to organize a workplace inclusion.[Penelitian ini membahas pengelolaan tenaga kerja difabel (diversity management) di PT. Trans Retail Indonesia serta faktor pendukung dan penghambat dalam pelaksanaan pengelolaan tenaga kerja penyandang disabilitas yang diterapkan oleh perusahaan dalam mewujudkan tempat kerja yang inklusif. Ini adalah penelitian kualitatif yang mengumpulkan data dari literatur, wawancara, dan observasi. Analisis dimulai dari pemahaman perusahaan mengenai tenaga kerja difabel, pengadaan tenaga kerja, pembinaan tenaga kerja, pemberian balas-jasa dan pemeliharaan tenaga kerja. Penelitian menemukan faktor pendukung pengelolaan tenaga kerja berupa kerjasama stakesholders, dukungan rekan kerja, pendampingan serta konseling bagi karyawan difabel. Sedangkan faktor penghambatnya adalah komunikasi, dukungan sejawat, tenaga profesional dan produktivitas kerja karyawan difabel yang mengancam keberlanjutan kerja mereka. Meskipun demikian, PT. Trans Retail Indonesia dapat dianggap memiliki modal yang cukup untuk mengembangkan diversity management dalam upaya mewujudkan workplace inclusion. ]